PEMBUATAN PUDING BERBAHAN DASAR DAUN KELOR SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA SINDANGMULYA - Wertanala, Aldi; Sikki, M. Ilyas; Supratno, Setyo (An-Nizam, 2024)
Malnutrition in children can cause delays in growth and development of the brain, bones, and emotional problems. This service program aims to provide understanding to the community, especially prospective parents, about stunting and the benefits of moringa Puding. Moringa leaf Puding has important benefits in preventing stunting, especially because of the very complete nutritional content of moringa leaves. Moringa leaves are rich in protein, vitamins A, C, E, calcium, and iron, all of which play an important role in supporting children's growth and development. The protein and calcium in moringa help in the formation of healthy bones and muscles, while iron plays a role in preventing anemia that can hinder growth. Vitamins A and C support the immune system, which is important for keeping children healthy and preventing infections that can hinder growth. The activity was conducted in two stages, starting with providing information on stunting and child nutrition. The next stage involved a demonstration of making moringa Puding. The results of this program were adequate knowledge about the types of nutritional intake that are good for children as a prevention of stunting and the community was able to make nutritious Puding made from moringa leaves.